Geometric calibration of seven degree of freedom Robotic Sample Holder for X-ray CT - Pekel, Erdal; Schaff, Florian; Dierolf, Martin; Pfeiffer, Franz; Lasser, Tobias (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
We present a geometric calibration method for integrating a seven degrees of freedom robotic arm as a sample holder within an existing laboratory X-ray computed tomography setup. We aim to provide a flexible sample holder that is able to execute non-standard and task-specific trajectories for complex samples. The calibration is necessary to identify the accurate pose of the sample which deviates from the expected pose due to inaccurate placement of the robotic arm. The robotic arm is integrated with a unified software package that allows for path planning, collision detection, geometric calibration and reconstruction of the sample. With our software the user is able to command the robotic arm to execute arbitrary trajectories for a given sample in a safe manner and output its reconstruction to the user. We present experimental results with a circular trajectory where the robotic sample holder achieves identical visual quality compared to a conventional sample holder.
CRIS-Team Scopus Importer:2023-03-08